Comparison of Free-Keyword and MeSH Headings in the Quick Drug Information Service by Using Electronic Journals in IMIC - SAWADA, Kozue (Igaku Toshokan, 2001)
The International Medical Information Center (IMIC) has been providing its Quick Drug Information Service (QDIS) by using ProQuest (PQ), a foreign-electronic-journal database, since April 1999. Users of the service can obtain a monthly list of bibliographic data selected from PQ by full-text searches for requested free-keywords. This paper compares of free-keywords and MeSH headings (PubMed) in QDIS and data availability.